Caracterização e análise das habilidades sociais e problemas de comportamento de crianças com autismo - Carvalho, Larissa Helena Zani Santos de (2012)
Autism is a behavioral syndrome that affects multiple areas of development, it is noteworthy changes among these deficits in social skills and behavior problems. National production in the area of autism has advanced in recent years, however there is still a lack of jobs in the area of social skills with this population. In the literature of other countries you can find many publications on this theme, but many studies are related to social skills training, without specification of appropriate procedures for assessing social skills deficits and problem behavior syndrome. Studies concerning the state of the art of these productions, show the need for more work with autistic impairment using multimodal assessment. Therefore the aim of this study was to characterize the repertoire of social skills and behavior problems in children with severe autism through a multimodal assessment, and perform functional analysis of deficits in social skills and behavior problems of the same. The study included 6 children, 3 males and 3 females, diagnosed with severe autism who were enrolled in a special education school in a remote town in Sao Paulo. Mothers and teacher responded to the Social Skills Ratting System (SSRS-BR) and an interview regarding social skills and behavior problems of children. Were also carried out a 30 recording of 1 children in 10 different environments in school. The results obtained from the SSRS-BR answered by mothers and teacher prevailed low level of social skills and high level of behavior problems. The results of the interviews showed that although these children have deficits in social skills compared with the normative sample, still have important social skills for interpersonal relationships. The recordings were made with the child who had lower levels of social skills and high in behavior problems, both in interviews and in SSRS. Functional analysis of the behaviors recorded allowed to list behavior problems competing with the social skills classes, and it was also possible to analyze the influence of the behavior patterns of teacher and caregiver in the child's repertoire. The results showed that children have deficits in social skills and behavior problems as reported in the literature, but also indicated the importance of tools that are able to identify specific needs of children with autism.